Tumours and cancers in Graeco-Roman times - Francois P. Retief; Louise Cilliers (Acta Theologica)
In Graeco-Roman times all tumours (Greek: onkoi, abnormal swellings) were considered to be of inflammatory origin, the result of unfavourable humoural fluxes, and caused by an extravascular outpouring of fluid into tissue spaces. The neoplastic nature of tumours is a more recent concept, barely two centuries old. In Hippocratic literature tumours were mainly classified as karkinômata, phumata and oidêmata. Phumata included a large variety of tumours, inflammatory and neoplastic in origin, and mostly benign (in modern terms), whilst oidêmata were soft, painless tumours and even included generalised oedema (dropsy). Although all categories possibly included occasional cancers, the vast majority of what appears to have been malignant tumours were called karkinoi/karkinômata (Latin: cancrum/carcinoma). There was however no recognition of benign and malignant, or primary and secondary tumours, in the modern sense.